Stroke rehabilitation robotic arm (wrist component) - Ang, Nathan Wee Kiat (Nanyang Technological University, 2024)
This project aims to enhance stroke rehabilitation by developing a robotic arm system that integrates diagnosis, training, and progress monitoring. Focused on enhancing post-stroke recovery, this solution combines strength, flexibility, dexterity, and coordination exercises into a streamlined, automated process. The approach advocates for patient independence and rehabilitation efficiency by enabling consistent exercise regimes without daily physiotherapy visits. By amalgamating arm and end-effector robotic devices, it aims to facilitate convenient and consistent recovery pathways, empowering patients to regain essential abilities and skills. The "Real-Time Diagnosis System" and "Adaptive Training System using Mechanical Solutions" are pivotal to this advancement, with the latter being the focus of this report. The project encompasses interdisciplinary expertise across sensor technology, data acquisition, mechanical engineering, biomedical insights, electrical engineering, software development, and systems integration. Utilising comprehensive engineering software, the design and implementation process is ensured to be robust, aiming to improve stroke recovery outcomes and patient quality of life.